2023
DOI: 10.3390/ijerph20043018
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of the COVID-19 Pandemic on the Perception and Use of Urban Green Spaces in Korea

Abstract: Faced with the prospect that the impact of the COVID-19 pandemic and climate change will be far-reaching and long-term, the international community is showing interest in urban green space (UGS) and urban green infrastructure utilization as a solution. In this study, we investigated how citizens’ perceptions and use of UGS have changed during COVID-19. We also collected their ideas on how UGS can raise its usability. As a result, more people became to realize the importance of UGS. In particular, the urban env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…The perceived increased interest in re-naturing and greening the cities by the municipalities and the general public, in particular after the pandemic, shows contrasting data from those found by Lorenzoni et al (2007). This reflects a possible shift in perspectives and a momentum for further advancing NBS integration and scholarship, in line with Li et al (2021) who found an increase in focus of NBS studies on greening interventions in urban areas, such as urban forests, and Kim et al (2023) who found increased usage of green urban spaces.…”
Section: Horizontal Integrationmentioning
confidence: 92%
“…The perceived increased interest in re-naturing and greening the cities by the municipalities and the general public, in particular after the pandemic, shows contrasting data from those found by Lorenzoni et al (2007). This reflects a possible shift in perspectives and a momentum for further advancing NBS integration and scholarship, in line with Li et al (2021) who found an increase in focus of NBS studies on greening interventions in urban areas, such as urban forests, and Kim et al (2023) who found increased usage of green urban spaces.…”
Section: Horizontal Integrationmentioning
confidence: 92%
“…In this context, though people had the freedom to decide whether to go out, many refrained from doing so owing to the prevailing social atmosphere and fear of infection. However, as the pandemic progressed, spaces such as parks became more popular because of their lower risk of infection and the opportunity they provided for maintaining physical and mental health through physical activity [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sustainability practices, such as environmental conservation and social responsibility, were linked to positive organizational behavior and performance, aligning with SDG 12 and SDG 13. Moreover, organizations in Kazakhstan can promote resilience and sustainability in positive organizational behavior to contribute towards achieving the SDGs (Cheng et al, 2021;Kim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%